Coprolites from the Late Triassic Kap Stewart Formation, Jameson Land, East Greenland: morphology, classification and prey inclusions - Hansen, Bitten Bolvig; Milàn, Jesper; Clemmensen, Lars B.; Adolfssen, Jan Schulz; Estrup, Eliza Jarl; Klein, Nicole; Mateus, Octávio; Wings, Oliver (Geological Society of London, 2015)
A description of the size, shape, structure, texture, contents and preservation of the 328 specimens